Application of composite monatomic catalyst, functional coating and application of functional coating

By using composite single-atom catalysts in black phosphorus-based anode materials, the formation and conversion of lithium polyphosphide, sodium and potassium polyphosphide are catalyzed, and the problems of reaction intermediate loss, low conductivity and slow reaction kinetics of black phosphorus-based anode materials are solved, thereby achieving higher cycle stability, specific capacity and rate performance.

CN119838621APending Publication Date: 2025-04-18INST OF ELECTRICAL ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510024837.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When black phosphorus is used as a negative electrode material, it faces irreversible loss of reaction intermediates, low conductivity and slow reaction kinetics, resulting in reduced Coulomb efficiency, poor reversibility, capacity attenuation and poor rate performance.

Method used

The electrochemical performance of the black phosphorus-based negative electrode is improved by catalyzing the generation and conversion of lithium polyphosphide, sodium and potassium polyphosphide.

Benefits of technology

The cyclic stability, specific capacity and rate performance of the black phosphorus negative electrode are significantly improved, while the diffusion of phosphides on the negative electrode surface is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838621A_ABST
    Figure CN119838621A_ABST
Patent Text Reader

Abstract

The invention provides application of a composite monatomic catalyst, a functional coating and application of the functional coating, and belongs to the field of diaphragms. The invention provides application of a composite monatomic catalyst in catalyzing lithium polyphosphate to generate lithium phosphide, catalyzing sodium polyphosphate to generate sodium phosphide or catalyzing potassium polyphosphate to generate potassium phosphide. The composite monatomic catalyst comprises a nitrogen-doped carbon material and a monatomic loaded on the nitrogen-doped carbon material, the single atoms are coordinated with nitrogen in the nitrogen-doped carbon material; the single atoms comprise one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium single atom, a molybdenum single atom, a magnesium single atom and an indium single atom. The composite metal monatomic catalyst adsorbs and catalyzes lithium / sodium / potassium polyphosphate to reduce the dissolution of a polyphosphate intermediate in an organic electrolyte and promote the conversion kinetics of converting the polyphosphate into insoluble phosphide, so that the electrochemical performance of a black phosphorus negative electrode is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of diaphragms, and in particular to the application of a composite single-atom catalyst, a functional coating and the application thereof. Background Art

[0002] With the continuous development of electronic devices, electric vehicles and energy storage stations, traditional graphite-based lithium-ion energy storage devices are increasingly unable to meet the needs of high energy density and fast charging capabilities.

[0003] Among the available materials, black phosphorus has a safe lithiation potential (relative to Li + / Li is about 0.7V), significantly reduced alkali metal ion diffusion barrier and high theoretical storage capacity, it is emerging as an ideal negative electrode material with high energy density and fast charging capability. However, when black phosphorus is directly used as a negative electrode material, it faces a series of severe challenges. First, the reaction intermediates of phosphorus materials (lithium polyphosphide / sodium / potassium, LixP y , Na x P y , K x P y ) in the electrolyte will lead to irreversible loss of active materials, further resulting in reduced Coulombic efficiency, poor reversibility and continuous capacity decay; secondly, the low conductivity of phosphorus materials themselves (about 10 -12 S·m -1 ) and slow reaction kinetics hinder the rapid transfer of electrode electrons / ions, and perform poorly at high current density. In addition, the multi-electron transfer and multi-phase conversion reactions of the phosphorus negative electrode are extremely sluggish in kinetics, causing large polarization phenomena, limiting high-rate performance, and leading to rapid capacity decay.

[0004] To solve the above problems, researchers usually use methods such as introducing carbon materials with good conductivity to load phosphorus materials or constructing a conductive carbon layer on the surface of the diaphragm. Although these methods can solve the problem of low inherent conductivity of phosphorus materials themselves, and effectively inhibit the diffusion of soluble polyphosphides, they can physically block polysulfides and improve the utilization rate of active substances. However, the van der Waals force between non-polar carbon materials and polar polyphosphides is relatively weak, and the adsorption capacity of polyphosphides is poor, resulting in rapid decay of the battery capacity. In addition, the slow conversion kinetics of lithium polyphosphide intermediates have an adverse effect on their electrochemical conversion, especially under high current density charging and discharging conditions, the conversion efficiency is low, which seriously affects its capacity and cycle stability. There is currently no effective solution to deal with these problems. Summary of the invention

[0005] The present invention provides an application of a composite single-atom catalyst, a functional coating and the application thereof. The composite single-atom catalyst of the present invention can improve the cycle stability, mass specific capacity and rate performance of a black phosphorus-based negative electrode battery.

[0006] The present invention provides an application of a composite single-atom catalyst in catalyzing lithium polyphosphide to generate lithium phosphide, catalyzing sodium polyphosphide to generate sodium phosphide, or catalyzing potassium polyphosphide to generate potassium phosphide; the composite single-atom catalyst comprises a nitrogen-doped carbon material and a single atom supported on the nitrogen-doped carbon material;

[0007] The single atom coordinates with nitrogen in the nitrogen-doped carbon material;

[0008] The single atom includes one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium single atom, a molybdenum single atom, a magnesium single atom and an indium single atom.

[0009] The present invention provides a functional coating, which comprises the following components in parts by mass:

[0010] 1 to 3 parts of composite single atom catalyst;

[0011] 1 to 3 parts of conductive material;

[0012] 0.5-2 parts of polymer resin;

[0013] The composite single-atom catalyst comprises a nitrogen-doped carbon material and a single atom supported on the nitrogen-doped carbon material;

[0014] The single atom coordinates with nitrogen in the nitrogen-doped carbon material;

[0015] The single atom includes one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium single atom, a molybdenum single atom, a magnesium single atom and an indium single atom.

[0016] Preferably, the nitrogen-doped carbon material comprises nitrogen-doped carbon nanotubes.

[0017] Preferably, the method for preparing the composite single-atom catalyst comprises the following steps:

[0018] The carbon material, metal phthalocyanine and water are mixed and then annealed to generate a reduction reaction, thereby obtaining the composite single-atom catalyst;

[0019] The metal phthalocyanine includes one or more of titanium phthalocyanine, manganese phthalocyanine, iron phthalocyanine, cobalt phthalocyanine, nickel phthalocyanine, niobium phthalocyanine, molybdenum phthalocyanine, magnesium phthalocyanine and indium phthalocyanine.

[0020] Preferably, the mixing comprises:

[0021] dispersing the carbon material in water to obtain a dispersion;

[0022] The dispersion is mixed with metal phthalocyanine and then ball milled.

[0023] Preferably, the concentration of the dispersion is 10 to 50 g·L -1 .

[0024] Preferably, the mass ratio of the carbon material to the metal phthalocyanine is 1:1.5-4.

[0025] Preferably, the annealing treatment temperature is 800-1000° C., and the holding time is 3-5 hours.

[0026] The present invention also provides the use of the functional coating described in the above technical solution in an alkali metal ion battery or an alkali metal ion capacitor, wherein the functional coating is located on the negative electrode side surface of the diaphragm in the alkali metal ion battery and the alkali metal ion capacitor and / or the functional coating is coated on the surface of the negative electrode in the alkali metal ion battery and the alkali metal ion capacitor;

[0027] The negative electrode in the alkali metal ion battery and the alkali metal ion capacitor contains black phosphorus.

[0028] Preferably, the negative electrode in the alkali metal ion battery and alkali metal ion capacitor comprises black phosphorus and / or a black phosphorus-carbon composite.

[0029] The electronic configuration and valence electron number of metal single atoms have a significant impact on their catalytic performance. For example, the d orbital electronic structure of transition metal elements determines the interaction mode and intensity between them and reactant molecules. The d orbital electrons of metal atoms that are not filled with d orbitals can participate in the bonding or electron transfer process of reactants, thereby affecting the progress of catalytic reactions. The electronic structures of single-atom titanium, single-atom manganese, single-atom iron, single-atom cobalt, single-atom nickel, single-atom niobium, and single-atom molybdenum selected by the present invention are suitable for interacting with polyphosphides, thereby showing good activity in catalytic reactions. In addition, single-atom magnesium and single-atom indium can form strong interactions with polyphosphide lithium / sodium / potassium, promoting the adsorption and conversion capabilities of polyphosphide lithium / sodium / potassium on its surface. In addition, the nitrogen atoms in the nitrogen-doped carbon material have a high electronegativity, which can enhance the electron cloud density of the metal single atom and improve its adsorption and activation ability for lithium polyphosphide / sodium / potassium molecules. Therefore, the nitrogen-coordinated metal single atom catalyst exhibits excellent catalytic performance in the redox reaction of lithium polyphosphide / sodium / potassium to lithium phosphide / sodium / potassium.

[0030] Therefore, the composite metal single-atom catalyst of the present invention can be adsorbed (physical adsorption is achieved on carbon materials, and chemical adsorption is achieved by the coordination of nitrogen atoms to single-atom active centers): the outer electron orbit of the metal atom has unpaired electrons or is not fully occupied, and has a strong electron affinity, and can form chemical bonds or electron pair interactions with lithium polyphosphide / sodium / potassium molecules; the metal atoms are evenly distributed on the surface of the carbon material, and more active sites are exposed to fully contact with lithium polyphosphide / sodium / potassium, and agglomeration is reduced; the smaller steric hindrance is conducive to the approach and Adsorption and chemical bonding (including covalent bonding to make lithium polyphosphide / sodium / potassium stable adsorption, or non-covalent bonding such as hydrogen bonding, van der Waals force, and electrostatic effect to assist adsorption) to achieve the adsorption of lithium polyphosphide / sodium / potassium) and catalysis of lithium polyphosphide / sodium / potassium to reduce the dissolution of lithium polyphosphide / sodium / potassium and promote the conversion kinetics of lithium polyphosphide / sodium / potassium into insoluble lithium phosphide / sodium / potassium in organic electrolyte, thereby significantly improving the electrochemical performance of black phosphorus negative electrode, achieving higher specific capacity and rate performance, and inhibiting the diffusion of phosphide on the negative electrode surface.

[0031] The present invention coats a functional coating of single-atom catalyst material based on nitrogen-doped carbon material and conductive carbon black on the surface of the diaphragm. The functional diaphragm can be used to inhibit the shuttling of lithium / sodium / potassium polyphosphides and promote the electrochemical conversion of black phosphorus lithium / sodium / potassium conversion, thereby improving the cycle stability and rate performance of the black phosphorus negative electrode energy storage device.

[0032] The present invention innovatively uses a diaphragm with a metal single-atom catalyst to improve the performance of a black phosphorus negative electrode.

[0033] The reactant raw materials and instruments and equipment used in the preparation process of the present invention are simple and easy to obtain, safe and non-toxic, and can be mass-produced. Whether used as a negative electrode material (forming a coating structure with black phosphorus to improve the conductivity and anti-expansion stability of phosphorus-based negative electrode materials; forming a PC bond with black phosphorus to reduce the oxidation of oxygen and water environments on phosphorus electrodes and improve the stability of materials in the air; through adsorption and catalysis of the conversion of soluble polyphosphides, not only can the dissolution of lithium phosphide / sodium / potassium products in the cycle process be inhibited, but also the direct contact between active materials and electrolytes can be avoided, thereby improving the cycle performance, stability, and rate performance of ion batteries, increasing the phosphorus loading in the electrode, and having excellent charge and discharge performance) or a diaphragm modification layer, it has a great role in promoting the large-scale commercial application of black phosphorus negative electrode energy storage devices.

[0034] The functional diaphragm prepared by the present invention can optimize the battery structure, and the assembled alkali metal ion capacitor full battery has higher performance, providing a new solution for the development of alkali metal ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1This is a transmission electron microscope image of the SATi-CNT obtained in Example 1 of the present invention;

[0036] Figure 2 This is the energy dispersive X-ray spectrum of SATi-CNT obtained in Example 1 of the present invention;

[0037] Figure 3 This is a spherical aberration electron microscope image of SATi-CNT obtained in Example 1 of the present invention;

[0038] Figure 4 This is a SEM image of the cross section of the SATi-CNT functional diaphragm obtained in Example 1 of the present invention;

[0039] Figure 5 The black phosphorus negative electrode|| lithium half-cell with different separators in Example 1 of the present invention is at 0.5A·g -1 Cycle performance diagram below;

[0040] Figure 6 The results of lithium ion full battery rate performance test of the soft pack battery assembled with the SATi-CNT functional separator, black phosphorus negative electrode and lithium cobalt oxide positive electrode in Example 1 of the present invention and the soft pack battery assembled with the CNT modified separator under the same conditions;

[0041] Figure 7 This is a transmission electron microscope image of the SAFe-CNT obtained in Example 2 of the present invention;

[0042] Figure 8 This is the energy dispersive X-ray spectrum of SAFe-CNT obtained in Example 2 of the present invention;

[0043] Fig. 9 This is a spherical aberration electron microscope image of the SAFe-CNT obtained in Example 2 of the present invention;

[0044] Fig.10 This is a SEM image of the surface of the SAFe-CNT functional diaphragm obtained in Example 2 of the present invention;

[0045] Fig.11 The black phosphorus negative electrode|| lithium half-cell with different separators in Example 2 of the present invention is at 0.5A·g -1 The cycle performance diagram below. DETAILED DESCRIPTION

[0046] The present invention provides an application of a composite single-atom catalyst in catalyzing lithium polyphosphide to generate lithium phosphide, catalyzing sodium polyphosphide to generate sodium phosphide, or catalyzing potassium polyphosphide to generate potassium phosphide; the composite single-atom catalyst comprises a nitrogen-doped carbon material and a single atom supported on the nitrogen-doped carbon material;

[0047] The single atom coordinates with nitrogen in the nitrogen-doped carbon material;

[0048] The single atom includes one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium single atom, a molybdenum single atom, a magnesium single atom and an indium single atom.

[0049] In the present invention, the nitrogen-doped carbon material preferably includes nitrogen-doped carbon nanotubes. Carbon nanotubes have a high specific surface area and good electrical conductivity, can effectively disperse metal atoms, and promote the transfer of electrons.

[0050] In the present invention, the method for preparing the composite single-atom catalyst preferably comprises the following steps:

[0051] The carbon material, metal phthalocyanine and water are mixed and then annealed to generate a reduction reaction, thereby obtaining the composite single-atom catalyst;

[0052] The metal phthalocyanine includes one or more of titanium phthalocyanine, manganese phthalocyanine, iron phthalocyanine, cobalt phthalocyanine, nickel phthalocyanine, niobium phthalocyanine, molybdenum phthalocyanine, magnesium phthalocyanine and indium phthalocyanine.

[0053] In the present invention, the mixing preferably includes: dispersing the carbon material in water to obtain a dispersion; and mixing the dispersion with the metal phthalocyanine and then ball milling.

[0054] In the present invention, the concentration of the carbon material in the dispersion is preferably 10 to 50 g·L -1 In a specific embodiment of the present invention, the concentration of the carbon material in the dispersion can be 10 g / L -1 , 20gL -1 , 30gL -1 40gL -1 or 50gL -1 ;

[0055] In the present invention, the mass ratio of the carbon material to the metal phthalocyanine is preferably 1:1.5-4. In a specific embodiment of the present invention, the mass ratio of the carbon material to the metal phthalocyanine can be 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4. The metal phthalocyanine includes one or more of titanium phthalocyanine, manganese phthalocyanine, iron phthalocyanine, cobalt phthalocyanine, nickel phthalocyanine, niobium phthalocyanine, molybdenum phthalocyanine, magnesium phthalocyanine and indium phthalocyanine.

[0056] In the present invention, during the ball milling, the mixed mixture is preferably placed in an agate grinding jar purified with 99.999% high-purity argon gas, sealed, and then placed in a high-energy ball mill; the ball milling is preferably performed in an inert environment.

[0057] In the present invention, the mass ratio of the grinding balls used in the ball mill and the mixture obtained by mixing is preferably 100-150:1. In a specific embodiment of the present invention, the mass ratio can be 120:1, 130:1, 140:1 or 150:1; the rotation speed of the ball mill is preferably 400-600rpm. In a specific embodiment of the present invention, the rotation speed of the ball mill can be 400rpm, 450rpm, 500rpm, 550rpm or 600rpm.

[0058] The metal phthalocyanine and carbon nanotubes are self-assembled by mechanical chemical engineering strategy (ball milling), so that the metal phthalocyanine is fixed on the carbon nanotubes.

[0059] In the present invention, the temperature of the annealing treatment is preferably 800-1000°C, and the holding time is preferably 3-5h; in a specific embodiment of the present invention, the temperature of the annealing treatment can be 800°C, 850°C, 900°C, 950°C or 1000°C; the annealing time can be 3h, 3.5h, 4h, 4.5h or 5h. The heating rate to the annealing temperature is preferably 4-6°C·min -1 In a specific embodiment of the present invention, the heating rate may be 4°C·min -1 、4.5℃min -1 、5℃min -1 、5.5℃min -1 or 6℃min -1 .

[0060] The present invention reduces metal atoms to form single atoms through annealing treatment, nitrogen is doped into the carbon material, and the single atoms are stabilized in the carbon material through nitrogen coordination.

[0061] After the annealing treatment, the method preferably further comprises: performing solid-liquid separation on the obtained product, and then washing and drying the obtained solid to obtain the composite single-atom catalyst.

[0062] In the present invention, the solid-liquid separation method is preferably centrifugation, and the washing preferably includes washing with hydrochloric acid and water in sequence; the temperature of the hydrochloric acid is preferably 25 to 70°C, and the concentration is preferably 0.5 to 2 mol·L -1 In a specific embodiment of the present invention, the temperature of the hydrochloric acid may be 25°C, 30°C, 40°C, 50°C, 60°C or 70°C; the concentration of the hydrochloric acid may be 0.5 molL -1 , 1molL -1 , 1.5molL -1 or 2molL -1 .

[0063] The present invention also provides a functional coating, which comprises the following components in parts by mass:

[0064] 1 to 3 parts of composite single atom catalyst;

[0065] 1 to 3 parts of conductive material;

[0066] 0.5-2 parts of polymer resin;

[0067] The composite single-atom catalyst comprises a nitrogen-doped carbon material and a single atom supported on the nitrogen-doped carbon material;

[0068] The single atom coordinates with nitrogen in the nitrogen-doped carbon material;

[0069] The single atom includes one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium phthalocyanine, a molybdenum phthalocyanine, a magnesium single atom and an indium single atom.

[0070] In terms of mass fractions, the components of the functional coating include 1 to 3 parts of a composite single-atom catalyst. In a specific embodiment of the present invention, the mass fraction of the composite single-atom catalyst may be 1 part, 2 parts or 3 parts;

[0071] In the present invention, the nitrogen-doped carbon material in the composite single-atom catalyst and the preparation method of the composite single-atom catalyst have been discussed above and will not be repeated here.

[0072] In terms of mass fraction, the components of the functional coating include 1 to 3 parts of a conductive material. In a specific embodiment of the present invention, the mass fraction of the conductive material may be 1 part, 2 parts or 3 parts; the conductive material preferably includes conductive carbon black;

[0073] In terms of weight percentage, the components of the functional coating include 0.5 to 2 parts of a polymer resin. In a specific embodiment of the present invention, the weight percentage of the polymer resin may be 0.5 parts, 1 parts, 1.5 parts or 2 parts; the polymer resin preferably includes polyvinylidene fluoride.

[0074] In the present invention, the drying temperature is preferably 50 to 70°C.

[0075] The present invention also provides the use of the functional coating described in the above technical solution in an alkali metal ion battery or an alkali metal ion capacitor, wherein the functional coating is located on the negative electrode side surface of the diaphragm in the alkali metal ion battery and the alkali metal ion capacitor and / or the functional coating is coated on the surface of the negative electrode in the alkali metal ion battery and the alkali metal ion capacitor;

[0076] The negative electrode in the alkali metal ion battery and the alkali metal ion capacitor contains black phosphorus.

[0077] In the present invention, the method for preparing the functional diaphragm comprises the following steps:

[0078] The composite metal single atom catalyst, conductive material, polymer resin and organic solvent are mixed and coated on the diaphragm, and then dried to obtain the functional diaphragm.

[0079] In the present invention, the organic solvent preferably includes N-methylpyrrolidone; the solid content of the mixed slurry is preferably 10-40wt%. In a specific embodiment of the present invention, the solid content can be 10wt%, 20wt%, 30wt% or 40wt%.

[0080] In the present invention, the coating method preferably includes ball milling.

[0081] In the present invention, the ion battery preferably includes a lithium ion battery, a sodium ion battery or a potassium ion battery.

[0082] In the present invention, the carbon of the black phosphorus-carbon composite preferably includes one or more of graphene, graphite, carbon nanotubes and carbon nanofibers.

[0083] The application of the composite single-atom catalyst, the functional coating and its application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0084] Example 1

[0085] A series of single-atom metal electrocatalysts loaded on multi-walled carbon nanotubes (inner diameter 5-12 nm, outer diameter 30-50 nm) were synthesized by high-energy ball milling on a full-dimensional planetary ball mill using a simple, efficient and high-yield mechanochemical method.

[0086] First, 0.40g of multi-walled carbon nanotubes were completely dispersed in 20.0mL of deionized water using ultrasonic treatment. Subsequently, titanium phthalocyanine was added according to the optimized carbon nanotube / titanium phthalocyanine mass ratio of 3:7 (w / w), and high-speed stirring was continued for 10min. It was then placed in a 250.0mL agate grinding tank, cleaned with high-purity Ar (99.999%) for 20min and sealed. 18.29g of agate grinding balls with different diameters (6.0, 10.0 and 20.0mm, mass ratio of 1:2:4) were used and milled at 500rpm for 24h. Natural agate material (with excellent heat dissipation) and 20.0mL of water were selected to ensure that the temperature of the entire grinding process was kept below 35°C to effectively prevent oxidation due to temperature increase. After ball milling, it was dried and then the resulting precursor was spun at 5°C min -1The temperature was raised from room temperature to 800°C and kept at this temperature for 3 h for annealing. The resulting mixture was centrifuged repeatedly and 1 mol·L -1 The mixture was washed with HCl and water, and the HCl was heated in a water bath at 70°C for 1 min beforehand, and then vacuum dried at 90°C for 4 h to obtain nitrogen-doped titanium single-atom carbon material (SATi-CNT).

[0087] The modified diaphragm was prepared by blade coating. Specifically, SATi-CNT, conductive carbon black and polyvinylidene fluoride were mixed with N-methylpyrrolidone in a mass ratio of 6:3:1, and then the resulting slurry (solid content in the slurry was 20wt%) was evenly coated on the surface of Celgard2500 diaphragm, and then dried at 60°C for 12h to obtain a SATi-CNT functional diaphragm with a coating thickness of 5μm.

[0088] Figure 1 This is a transmission electron microscope image of the SATi-CNT obtained in Example 1.

[0089] from Figure 1 It can be seen that the structure of the carbon nanotubes themselves is maintained, and there are no obvious particles attached to the surface, which indicates that there are no metal particle clusters and incompletely reacted precursors in the material.

[0090] Figure 2 This is the energy dispersive X-ray spectrum of the SATi-CNT obtained in Example 1.

[0091] Figure 2 The energy dispersive X-ray spectrum shows that C, N and Ti elements are evenly distributed on the surface of carbon nanotubes.

[0092] Figure 3 This is the spherical aberration electron microscope image of the SATi-CNT obtained in Example 1.

[0093] from Figure 3 It can be seen that the bright spots evenly distributed on its surface are single atomic titanium, which further confirms the successful preparation of single atomic titanium and the formation of no metal clusters and metal particles.

[0094] The surface morphology of the SATi-CNT functional diaphragm was observed using a scanning electron microscope. Figure 4 .

[0095] Depend on Figure 4 It can be seen that the titanium single atom carbon nanotubes, conductive carbon black and polytetrafluoroethylene in the membrane surface coating have good compatibility and are evenly distributed.

[0096] The obtained SATi-CNT functional separator was cut into 17 mm discs, and a CR2025 button cell (electrolyte: 1 M LiPF6 DMC / DEC / EC (1 / 1 / 1 v / v / v)) was assembled with a black phosphorus electrode and a lithium sheet. -1 The cycle test was carried out, and the lithium||black phosphorus half-cells with different separators were also cycled under the same conditions. The results are as follows Figure 5 shown. Figure 5 In the figure, the unmodified membrane refers to the Celgard2500 membrane; the preparation method of the carbon nanotube modified membrane is as follows: multi-walled carbon nanotubes (inner diameter of 5-12 nm, outer diameter of 30-50 nm), conductive carbon black and polyvinylidene fluoride are mixed with N-methylpyrrolidone in a mass ratio of 6:3:1, and then the resulting slurry (solid content in the slurry is 20wt%) is evenly coated on the surface of the Celgard2500 membrane, and then dried at 60°C for 12h to obtain a carbon nanotube (CNT) modified membrane with a coating thickness of 5μm.

[0097] from Figure 5 It can be seen that the SATi-CNT functional diaphragm prepared by the present invention exhibits the most excellent discharge capacity (2281 mAh / g) and capacity retention rate (73%).

[0098] The obtained SATi-CNT functional separator, black phosphorus negative electrode and lithium cobalt oxide positive electrode were assembled into a soft pack battery (mass of lithium cobalt oxide:mass of black phosphorus / carbon composite=5:1, mass ratio of black phosphorus to carbon in black phosphorus / carbon composite was 7:3, electrolyte was 1MLiPF6 DMC / DEC / EC (1 / 1 / 1v / v / v)) and a soft pack battery assembled with CNT modified separator under the same conditions for lithium ion full battery rate performance test. The results are as follows Figure 6 As shown in Table 1. Among them, Figure 6 (a) is the rate performance result of the full battery test assembled with SATi-CNT functional separator. Figure 6 (b) shows the rate performance test results of the full battery assembled with CNT modified separator under the same conditions. The discharge capacity is calculated uniformly according to the mass of active material of the lithium cobalt oxide positive electrode.

[0099] Depend on Figure 6 As shown in Table 1, under low current density, the discharge specific capacity of the whole battery is not lost, but as the rate performance increases, the capacity of the whole battery containing SATi-CNT functional separator is higher, which indicates that the introduction of SATi-CNT accelerates the kinetics of the lithiation process of the black phosphorus negative electrode and accelerates the conversion process of lithium polyphosphide intermediates.

[0100] Table 1 Discharge specific capacity of full cells assembled with SATi-CNT functional separators and full cells assembled with CNT modified separators

[0101]

[0102]

[0103] Example 2

[0104] On a full-dimensional planetary ball mill, with the help of high-energy ball milling, a series of single-atom metal electrocatalysts loaded on multi-walled carbon nanotubes (inner diameter of 5-12nm, outer diameter of 30-50nm) were synthesized using a simple, efficient and high-yield mechanochemical method.

[0105] First, 0.40g of multi-walled carbon nanotubes were completely dispersed in 20.0mL of deionized water by ultrasonic treatment. Then, iron phthalocyanine was added according to the optimized mass ratio of iron phthalocyanine to carbon nanotubes of 3:7 (w / w), and high-speed stirring was continued for 10min. It was then placed in a 250.0mL agate grinding tank, cleaned with high-purity Ar (99.999%) for 20min and sealed. 18.29g of agate grinding balls with different diameters (6.0, 10.0 and 20.0mm, mass ratio of 1:2:4) were used and milled at 500rpm for 24h. Natural agate material with good heat dissipation performance and 20.0mL of water were selected to ensure that the temperature was maintained below 35°C throughout the grinding process to effectively prevent oxidation caused by temperature increase. After ball milling, it was dried and then the resulting precursor was quenched at 5°C min -1 The mixture was heated from room temperature to 800°C at a heating rate and kept at this temperature for 3 h for annealing. -1 The mixture was washed with HCl and water, the HCl was heated in a water bath at 70°C for 1 min, and then vacuum dried at 90°C for 4 h to obtain nitrogen-doped iron single-atom carbon material (SAFe-CNT).

[0106] The modified diaphragm was prepared by blade coating. Specifically, SAFe-CNT, conductive carbon black and polyvinylidene fluoride were mixed with N-methylpyrrolidone in a mass ratio of 6:3:1, and then the resulting slurry (solid content in the slurry was 20wt%) was evenly coated on the surface of Celgard2500 diaphragm, followed by drying at 60°C for 12h, thereby obtaining a SATi-CNT functional diaphragm with a coating thickness of 5μm.

[0107] Figure 7 This is a transmission electron microscope image of the SAFe-CNT obtained in Example 2.

[0108] from Figure 7It can be seen that it maintains the original structure of the carbon nanotubes and there are no obvious particles attached to the surface, which indicates that there are no metal particle clusters and incompletely reacted precursors in the material.

[0109] Figure 8 This is the energy dispersive X-ray spectrum of the SAFe-CNT obtained in Example 2.

[0110] Depend on Figure 8 The energy dispersive X-ray spectrum shows that C, N, and Fe elements are evenly distributed on the surface of carbon nanotubes.

[0111] Fig. 9 This is the spherical aberration electron microscope image of the obtained SAFe-CNT.

[0112] from Fig. 9 It can be seen that the bright spots evenly distributed on its surface are single atomic iron, which further confirms the successful preparation of single atomic iron and the absence of metal clusters and metal particles.

[0113] The surface morphology of the SATi-CNT functional diaphragm was observed using a scanning electron microscope. Fig.10 .

[0114] Depend on Fig.10 It can be seen that the iron single-atom carbon nanotubes, conductive carbon black and polytetrafluoroethylene in the membrane surface coating have good compatibility and are evenly distributed.

[0115] The obtained SATi-CNT functional separator was cut into 17 mm discs, and a CR2025 button cell (electrolyte: 1 M LiPF6 DMC / DEC / EC (1 / 1 / 1 v / v / v)) was assembled using a black phosphorus electrode and a lithium sheet. -1 Cyclic tests were performed on lithium||black phosphorus half-cells with different separators under the same conditions. The results are shown in Fig.11 shown.

[0116] from Fig.11 It can be seen that the SAFe-CNT functional diaphragm prepared by the present invention in Example 2 exhibits the most excellent discharge capacity (2304.42 mAh / g) and capacity retention rate (70.16%).

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Use of a composite single-atom catalyst in catalyzing lithium polyphosphide to generate lithium phosphide, catalyzing sodium polyphosphide to generate sodium phosphide, or catalyzing potassium polyphosphide to generate potassium phosphide; the composite single-atom catalyst comprises a nitrogen-doped carbon material and a single atom supported on the nitrogen-doped carbon material; The single atom coordinates with nitrogen in the nitrogen-doped carbon material; The single atom includes one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium single atom, a molybdenum single atom, a magnesium single atom and an indium single atom.

2. A functional coating, characterized in that: The coating comprises the following components in parts by mass: 1 to 3 parts of composite single atom catalyst; 1 to 3 parts of conductive material; 0.5-2 parts of polymer resin; The composite single-atom catalyst comprises a nitrogen-doped carbon material and a single atom supported on the nitrogen-doped carbon material; The single atom coordinates with nitrogen in the nitrogen-doped carbon material; The single atom includes one or more of a titanium single atom, a manganese single atom, an iron single atom, a cobalt single atom, a nickel single atom, a niobium single atom, a molybdenum single atom, a magnesium single atom and an indium single atom.

3. The functional coating according to claim 2, characterized in that The nitrogen-doped carbon material includes nitrogen-doped carbon nanotubes.

4. The functional coating according to claim 2 or 3, characterized in that The preparation method of the composite single-atom catalyst comprises the following steps: The carbon material, metal phthalocyanine and water are mixed and then annealed to generate a reduction reaction, thereby obtaining the composite single-atom catalyst; The metal phthalocyanine includes one or more of titanium phthalocyanine, manganese phthalocyanine, iron phthalocyanine, cobalt phthalocyanine, nickel phthalocyanine, niobium phthalocyanine, molybdenum phthalocyanine, magnesium phthalocyanine and indium phthalocyanine.

5. The functional coating according to claim 4, characterized in that The mixing includes: dispersing the carbon material in water to obtain a dispersion; The dispersion is mixed with metal phthalocyanine and then ball milled.

6. The functional coating according to claim 5, characterized in that The concentration of the dispersion is 10 to 50 g·L -1 .

7. The functional coating according to claim 5 or 6, characterized in that: The mass ratio of the carbon material to the metal phthalocyanine is 1:1.5-4.

8. The functional coating according to claim 4, characterized in that: The annealing treatment is carried out at a temperature of 800 to 1000° C. and a heat preservation time of 3 to 5 hours.

9. Use of the functional coating according to any one of claims 2 to 9 in an alkali metal ion battery or an alkali metal ion capacitor, characterized in that: The functional coating is located on the negative electrode side surface of the separator in the alkali metal ion battery and the alkali metal ion capacitor and / or the functional coating is coated on the surface of the negative electrode in the alkali metal ion battery and the alkali metal ion capacitor; The negative electrode in the alkali metal ion battery and the alkali metal ion capacitor contains black phosphorus.

10. The use according to claim 9, characterized in that: The negative electrode in the alkali metal ion battery and the alkali metal ion capacitor includes black phosphorus and / or a black phosphorus-carbon composite.